2009
DOI: 10.1542/peds.2008-3586f
|View full text |Cite
|
Sign up to set email alerts
|

The Use of BMI in the Clinical Setting

Abstract: BMI has been recommended for evaluating overweight and obesity in children and adolescents in the clinical setting. Definitions of overweight and obesity are based on percentile cutoff points. There are both strengths and limitations of BMI for this use. The strengths include the fact that BMI is cheap and relatively easy to use. The weaknesses include the fact that BMI percentiles are not widely used, and categorization of BMI percentiles may not adequately define risk of comorbid conditions. In addition, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 33 publications
1
113
0
1
Order By: Relevance
“…For example, individuals with increased muscle mass may also have increased BMI (33) . On the other hand, individuals with decreased lean body mass and increased adiposity may also be misclassified by assessment with BMI (33) . Alvero-Cruz et al (34) showed that the FMI had higher accuracy for overweight screening than BMI.…”
Section: Defining Overweight and Obesitymentioning
confidence: 99%
“…For example, individuals with increased muscle mass may also have increased BMI (33) . On the other hand, individuals with decreased lean body mass and increased adiposity may also be misclassified by assessment with BMI (33) . Alvero-Cruz et al (34) showed that the FMI had higher accuracy for overweight screening than BMI.…”
Section: Defining Overweight and Obesitymentioning
confidence: 99%
“…The assessment most widely used is the body mass index (BMI) [1], which is not a sensitive indicator of either the amount or the distribution of body fat in this age group [6,7,8]. Body fat distribution is important due to the known association between some diseases and a greater accumulation of abdominal fat, regardless of age and the amount of total body fat [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Partiendo de la definición de obesidad (exceso de tejido adiposo) de la OMS, y que afecta de manera adversa la salud y el bienestar (28), los indicadores idóneos para definirla deben ser aquellos que cuantifiquen la magnitud del tejido adiposo (29), de ahí que la definición ideal tendría que basarse en la estimación del porcentaje de grasa corporal (20). Sin embargo, las mediciones que se obtienen son del IMC, que representa tanto la masa grasa como la masa libre de grasa, por lo que es un indicador de peso y no de adiposidad (30). Por ello, se ha cuestionado el uso del IMC en poblaciones donde prevalece la estatura baja (31).…”
Section: Discussionunclassified